The Stickiness of Aggregate Consumption Growth in OECD Countries: A Panel Data Analysis - Gerdie Everaert; Lorenzo Pozzi (Tinbergen Institute, 2010)
This paper examines the sources of stickiness in aggregate consumption growth. We first derive a dynamic consumption equation which encompasses many recent developments in consumption theory: habit formation, intertemporal substitution effects, consumption based on current income, and non-separabilities between private consumption and both hours worked and government consumption.Next, we estimate this dynamic consumption equation for a panel of 15 OECD countries over the period 1972-2007 taking into account endogeneity issues and error cross-sectional dependence. To this end, we develop a generalised method of moments version of the common correlated effects pooled estimator and demonstrate its small sample behaviour using Monte Carlo simulations. The estimation results support the labour-consumption complementarity hypothesis but not the other forms of stickiness.
Keywords: C23; E21; 330; Sticky Consumption; Dynamic Panel; Cross-Sectional Dependence; Gesamtwirtschaftlicher Konsum; Konsumtheorie; Schätzung; OECD-Staaten